Houses of Culture as Places of/in Memory - Petra Chovancová (Ksiegarnia Akademicka Publishing, 2019)
This paper introduces key concepts of a preliminary project concerning houses of culture in former Czechoslovakia. Houses of culture used to be perceived as one of the signs, as well as a platform of establishing power during the communist era. The project will concentrate on various aspects of planning, building and managing houses of culture. In our research project we apply the “history from below” approach while viewing these Houses as a kind of “les Lieux de Mémoire” (places of memory). The chosen approach will require one to find historical witnesses and conduct a series of interviews with them in order to find out how houses of culture shaped their life during the communist era and, on the other hand, how people shaped the cultural life of these institutions.